2015
DOI: 10.3343/alm.2015.35.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the SLCO1B1 c.521T>C Variant Reveals Slight Influence on the Lipid-Lowering Efficacy of Statins

Abstract: BackgroundSeveral studies have focused on the association between the lipid-lowering efficacy of statins and the SLCO1B1 c.521T>C polymorphism; however, the results are conflicting. The effects of statins show significant variability between individuals. This meta-analysis aimed to investigate the effects of the SLCO1B1 c.521T>C polymorphism on the lipid-lowering effects of statins.MethodsWe systematically searched PubMed and Web of Science to screen relevant studies. Meta-analysis was performed to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
1
11
1
3
Order By: Relevance
“…Our study findings regarding SLCO1B1 521C were consistent with those observed in Heart Protection Study 15 and in the meta-analysis reported by Duo et al 14…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study findings regarding SLCO1B1 521C were consistent with those observed in Heart Protection Study 15 and in the meta-analysis reported by Duo et al 14…”
Section: Discussionsupporting
confidence: 92%
“…[14]: SLCO1B1 521C was associated with a diminished cholesterol-lowering response. The consistencies regarding the magnitude and direction of this effect not only support the validity of our study but also provide addition evidence supporting the central role of SLCO1B1 in the pharmacology of simvastatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimate that patients with both risk factors are likely to have a much higher chance of developing myopathy. In addition, it is worth noting that both the FDA and the UK Medicines and Healthcare products Regulatory Agency propose a 50% lower dose of simvastatin for patients who coadminister amlodipine -it is unknown how this practice will influence the clinical outcomes of simvastatin treatment, particularly in patients carrying the SLCO1B1 c.521T>C variant, who are less responsive to simvastatin [33,34]. In conclusion, SLCO1B1 geno typing may be critical for simvastatin users who unavoidably take CYP3A4 inhibitors such as amlodipine, in order to lower the risk of adverse effects and impaired drug efficacy.…”
Section: Discussionmentioning
confidence: 99%